How Wild is Iceland? Wilderness Quality with Respect to Nature-based Tourism - Olafsdottir, Rannveig; Runnström, Micael (Tourism Geographies, 2011)
The Icelandic highlands are one of the few places left in Europe where tourists can experience pristine wilderness. During the past decades the highlands have, however, witnessed a rapid expansion in natural resource exploitation. This study attempts to evaluate the pristine condition of Icelandic wilderness by testing different methods of identifying and analysing wilderness with respect to nature-based tourism. The wilderness areas were mapped with respect to proximity to anthropogenic structures (proximity analysis) as well as what is actually visible in the landscape in relation to topography (viewshed analysis). When analysed with respect to proximity, result maps indicate that wilderness covers a little less than 34 percent of Iceland. When assessed at a national scale, results from the viewshed analysis show similar results. However, evaluation of the two methods tested indicates that the viewshed analysis gives a more dynamic image of the Icelandic wilderness areas, whereas the proximity analysis simply highlights static buffer zones relative to the network of anthropogenic features. It is concluded that a viewshed analysis provides a more qualitative result regarding the Icelandic wilderness resource at a local scale with respect to nature-based tourism.